Competing Hermeneutics: The Martyr Murals at Santo Stefano Rotondo - Groarke, Louis F. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
The frescoed martyrdom murals at Santo Stefano Rotondo in Rome (c. 1582) have inspired much conflicting commentary down through the centuries. Painted by Niccolò Circignani (familiarly known as il Pomarancio), they feature gruesome, realistic renderings of torture scenes dating from the late Roman persecutions. Protestant and Catholic audiences have offered dramatically opposing evaluations of the harrowing subject matter on display. In this article, I report on and analyze the paintings from both a Protestant and a Catholic point of view. I want to show how a careful historical analysis can recover intentionality—the original purpose and aspirations embodied in an artwork—and, at the same time, make sense of incompatible readings of the very same visual content.